2004
DOI: 10.1111/j.1523-1755.2004.00749.x
|View full text |Cite
|
Sign up to set email alerts
|

Nonimmunologic complications and gene polymorphisms of immunoregulatory cytokines in long-term renal transplants

Abstract: We established an association of particular cytokine genotypes with nonimmunologic post-transplant complications. This supports an idea that assessment of cytokine SNPs may allow more accurate prediction of nonimmunologic complications and appropriate adjustment of pre-emptive treatments in long-term transplant patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 30 publications
0
15
2
Order By: Relevance
“…These two chronic diseases have been previously recognized as risk factors for DHF in Cubans [6]. Cytokines genes polymorphism has been associated with other viral infections outcome [42][43][44][45].…”
Section: Discussionmentioning
confidence: 97%
“…These two chronic diseases have been previously recognized as risk factors for DHF in Cubans [6]. Cytokines genes polymorphism has been associated with other viral infections outcome [42][43][44][45].…”
Section: Discussionmentioning
confidence: 97%
“…Cytokines have been shown to be implicated in the occurrence of AR of renal allografts, with different subtypes of cytokines having controversial effects (Azarpira et al, 2009). Cytokine gene polymorphisms have been associated with the development of both immunological and nonimmunological complications after renal transplantation (Babel et al, 2004). Cytokine production is associated with a risk of postoperative organ dysfunction as well as increased morbidity and mortality (Hadimioglu et al, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…The TGF-β1 cytokine concentration is likely higher in nephritis, which nephritis is one of the mortality causes in Lupus patients [4]. Furthermore, the increasing of TGF-β1 production may be projected to the severity of Lupus Nephritis [4, 5]. Another study showed that G915C polymorphism of TGFB1 gene is related to the progression of liver fibrosis in patients with chronic Hepatitis C [6].…”
Section: Introductionmentioning
confidence: 99%